Advances in hospitality and leisure. - Chen, Joseph S. (Advances in hospitality and leisure., 2019)
Advances in Hospitality and Leisure (AHL), a peer-reviewed research journal, has been published annually since 2004. AHL is indexed in Scopus and included in the Australian Business Deans Council (ABDC) journal quality list. International in focus, the series attempts to divulge innovative methods of inquiry so as to inspire new research topics that are vital and have been in large neglected in the context of hospitality, tourism, and leisure. It strives to address the needs of the populace willing to disseminate seminal ideas, concepts, and theories derived from scholarly inquiries. This fifteenth annual volume includes eight full papers and three research notes. Most articles deploy either a quantitative or qualitative approach to data collection while two present conceptual models. The scholarly works covered in the volume are contributed by reputable researchers from five nations. The authors of this publication come from America, Europe, Asia, Pacific, and Africa. Potential readers may retrieve useful articles to outline new research agendas, suggest viable topics for a dissertation work, and augment the knowledge of the new subjects of learning."